Stomata Profile Comparisons in Abaxial and Adaxial Zones of Dendrobium aphyllum and Arachnis flos-aeris Leaves - Febri Yuda Kurniawan; Agung Dwi Santoso (Biota, 2020)
Stomata activity in orchids is related to orchids' adaptation process to their environment. This study aimed to investigate the stomata profile, comprising of anatomical structure and density of the two orchids species, Dendrobium aphyllum, and Arachnis flos-aeris. Data was collected by printing the leaves' surface using glue and observed at 09.00 am and 09.00 pm, then analyzed using Image raster 3.0 software and MS. Excel. The stomata of D. aphyllum and A. flos-aeris were characterized by anomocytic type. Results showed that the highest stomata density was 1177.78 um2, found on the abaxial part of D. aphyllum. The adaxial leaves of both species were classified as low or no stomata. These two orchid species were epiphyte yet grow in different habitats. Arachnis flos-aeris exposed to direct sunlight tends to reduce transpiration rate, resulting in fewer stomata than D. aphyllum less exposed to sunlight.